Lung Cancer Ablation: Complications - Hiraki, Takao; Gobara, Hideo; Fujiwara, Hiroyasu; Ishii, Hiroaki; Tomita, Koji; Uka, Mayu; Makimoto, Satoko; Kanazawa, Susumu (Seminars in Interventional Radiology, 2013)
Although radiofrequency ablation for lung cancer is generally safe (with a mortality rate <1%), it may cause various complications. Common complications include pneumothorax, pleural effusion, and parenchymal hemorrhage. Although most complications can be treated conservatively or with minimal therapy, physicians should be aware of rare but serious complications. Potentially fatal complications include massive hemorrhage, intractable pneumothorax due to bronchopleural fistula, pulmonary artery pseudoaneurysm, systemic air embolism, and pneumonitis. Other serious complications include injury to the nearby tissues (e.g., brachial nerve plexus, phrenic nerve, diaphragm, and chest wall), needle tract seeding, lung abscess, empyema, and skin burn. Although cavitation of the ablation zone is usually insignificant clinically, such a cavity occasionally ruptures, leading to pneumothorax and bleeding. Cavities may also serve as a scaffold for fungal colonization. Precautions to minimize risk should be taken whenever possible. Nevertheless, serious complications may occur, and thus physicians should be aware of the appropriate treatments for these complications. This article reviews complications associated with lung cancer ablation.
Keywords: radiofrequency ablation; lung cancer; complication; interventional radiology